Mindfulness-based art interventions for students: a meta-analysis review of the effect on anxiety - Zhu, Zhihui; Xiao, Lin; Ahmad, Nor Aniza; Roslan, Samsilah; Burhanuddin, Nur Aimi Nasuha; Gao, Jianping; Huang, Cuihua (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Anxiety has become an important issue affecting students’ mental health. There is some evidence that mindfulness-based art interventions (MBAIs) can reduce students’ anxiety symptoms. However, some studies have shown the opposite view. Therefore, it is necessary to explore whether MBAIs are effective in alleviating students’ anxiety. In this meta-analysis, we chose 17 articles that met the criteria for inclusion, involving a total of 1548 participants, to figure out how big an impact the interventions had on student anxiety as a whole. The results show that MBAIs can reduce students’ anxiety (g = −0.387, p = 0.000). The effect size varies based on different moderators, including learning stage, sample size, intervention type, research design, measuring instrument, and intervention duration. Intervention type, research design, and measuring instrument are significant moderators. Specifically, the mindfulness-based art intervention (MBAI) showed stronger effects than the mandala coloring activity. Single-group experimental designs showed significantly higher effect sizes than studies that included a control group, and studies that used other measurement instruments had significantly higher effect sizes than those that used the State–Trait Anxiety Inventory. On this basis, the researchers put forward specific suggestions based on MBAIs to alleviate the anxiety of students from different educational backgrounds. However, due to the nascent nature of this field, the number of included articles is relatively small. The effectiveness of the research needs further testing.